The Effect of Work Ability and Work Discipline on Employee Performance at PT. Sooplai Indonesia (Warung Pintar Distribution) - Nuroin, Farhan; Fauzobihi, Fauzobihi; Supriyadi, Supriyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The flow of globalization that is getting faster continues to demand an employee to have good performance. Technological advances can shift employees who perform poorly by retiring early or taking a position. Employees are required to have adequate work skills and good work discipline so that their performance is maintained. This study aims to determine effect of work ability and work discipline on the performance of employees of PT Sooplai Indonesia (Warung Pintar Mediterania) either partially or simultaneously. This study used quantitative methods with survey methods and data collection techniques using questionnaires. The population in this study were employees of PT Sooplai Indonesia (Smart Distribution Warung), specifically for the Cakung warehouse, namely 94 people. The sample of this study used the slovin formula, namely 48 people. While the data analysis technique used is the classical assumption test, multiple regression, t test, F test and the coefficient of determination. The results showed that work ability and work discipline have a significant effect on the performance of employees of PT Sooplai Indonesia (Warung Pintar Distribution). Partially, work ability has a significant effect on the performance of employees of PT Sooplai Indonesia (Smart Distribution Warung), while work discipline has no significant effect on employee performance.